BIOGRAFI MISBAH DJALILAH SEBAGAI TOKOH PEJUANG PEREMPUAN DI SIAK SRI INDRAPURA (1926-2007) - Musfita Aini; Tugiman Tugiman; Asril Asril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The role of women in the historical trajectory of the struggle of theIndonesian people has not been much studied. One of the female figures who alsocontributed to the Indonesian people was Misbah Djalilah. This study aims todetermine: (1) To find out the life history of the Misbah Djalilah; (2) To find out thecharacter of Misbah Djalilah as a warrior in Siak Sri Indrapura in 1926-2007; (3) Tofind out the end of the struggle and the end of the history of the Misbah Djalilah. In thisstudy the authors used the historical method, which is a research method used to makea reconstruction of the past systematically and objectively by collecting data, evaluatingin detail the evidence to explain the facts and obtain strong conclusions. The results ofthis study are as follows: (1) Misbah Djalilah was born in Tanjung Pura Langkat, NorthSumatra on January 1, 1926. Tanjung pura is a sub-district in Langkat Regency, NorthSumatra. The name Misbah is given the full name Misbah. Follow the bint of H. Sa'ban.Misbah Djalilah since childhood has received the world of education. The Sultan senthim to study at HIS Siak and continued his education at Diniyah Putri Padang Panjang.(2) The figure of Misbah is described as follows: a. Misbah Involvement in the FujinkaiOrganization, b. Misbah Struggle Djalilah as members of class unity c, c. MisbahDjalilah during the Physical Revolution, d. Misbah Get Started as a Teacher in a publicschool in Selatbaru Bengkalis district (3) On January 17, 2007 he died at Ibnu SinaHospital Pekanbaru at 23:45 WIB after undergoing treatment for several days, due tofalling ill on January 1, 2007, and was buried on January 18 at Taman BahagiaKusuma Bhakti Veterans Cemetery Jl. Cold water, Marpoyan Pekanbaru.Key Words: Biography, Misbah Djalilah, Female Warrior, Siak Sri Indrapura